PRODUCTIVE PERFORMANCE OF CARROT AND COWPEA INTERCROPPING SYSTEM UNDER DIFFERENT SPATIAL ARRANGEMENTS AND POPULATION DENSITIES - GIORGIO MENDES RIBEIRO (Revista Caatinga, 2018)
Spatial arrangement and population density of component cultures, when well structured, may contribute to increased crop yields relative to monocultures. Thus, the objective of this work was to evaluate the productive performance of carrot and cowpea in an intercropping system under different spatial arrangements and population densities. This research was conducted on the “Rafael Fernandes” experimental farm of the Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró, RN, Brazil. The experimental design was a randomized complete block with four replicates, where the treatments were arranged in a 3 × 4 factorial scheme, in which the first factor was three spatial arrangements (2:2, 3:3, and 4:4) and the second factor was four different population densities of cowpea (100%, 80%, 60%, and 40% of the recommended population in the single crop RPSC). Rooster tree Calotropis procera (Ait.) R.Br., a spontaneous species of the „Caatinga‟ biome, was used as fertilizer. The characteristics evaluated in carrot were as follows: total and commercial productivity of roots and classified root production. The following characteristics were evaluated for cowpea: number of pods per square meter, length and yield of green pods, number of grains per pod, 100grain weight, and yield of green grains. The modified monetary advantage was used to evaluate the feasibility of the intercropped systems. Spatial arrangements between the component cultures did not influence the agroeconomic performance of the carrot-cowpea intercropping system. The highest agro-economic performance of the carrot-cowpea intercropping was obtained in the population of cowpea, which was 42% of the RPSC.